FREQUENCY OF LEFT VENTRICULAR THROMBUS IN PATIENTS WITH ACUTE ANTERIOR WALL MYOCARDIAL INFARCTION - SAJJAD, M; ULLAH, N; QURESHI, AE; ANUM, H; FAROOQ, U; DAR, WA (Biological and Clinical Sciences Research Journal, 2023)
Acute myocardial infarction (AMI) can be fatal and, if not, can result in many short- and long-term complications. Left ventricular thrombus (LVT) is an underrated complication that can lead to systemic embolization and, ultimately, stroke or end-organ damage. The current cross-sectional study is designed to determine the frequency of left ventricular thrombus after acute anterior wall myocardial infarction at the Department of Cardiology, Rehmatul-lil-Alameen Institute of Cardiology, Lahore, from 12-09-2020 to 11-03-2021. All patients of 20 to 60 years of either gender meeting the operational definition of the acute anterior wall were included. LV thrombus was diagnosed on echocardiography as an amorphous echogenic structure with variable shape and adherent to the endocardium. In this study, there were 87 cases; out of these, there were 57 (65.52%) males, and 30 (34.48%) females. The mean age of the subjects was 49.90±6.27 years. Out of 87 cases, 37 (42.53%) had a history of DM, 30 (45.98%) were hypertensive, and 31 (35.63%) were smokers. Left ventricular thrombus (LVT) was found in 16 (18.39%) cases. LVT was seen in 9 (15.79%) males vs. 7 (23.33%) females with p= 0.39. LVT was seen in 5 (13.51%) cases with DM and 11 (22%) with no DM, 7 (17.50%) cases with HTN, and 9 (19.15%) normotensives with p= 0.41 and 1.0. LVT was found in 5 (22.72%) cases with ejection fraction (EF) up to 40% and 11 (16.92%) cases with EF more than this with p= 0.18. Based on the results, the left ventricular thrombus is not uncommon after acute anterior wall MI and is nearly seen in every one out of five cases and is more common in cases with ejection fraction up to 40%.